Polyetheretherketone/poly (glycolic acid) blend scaffolds with biodegradable properties. Issue 14 (21st September 2016) - Shuai, Chenying; Wu, Ping; Zhong, Yancheng; Feng, Pei; Gao, Chengde; Huang, Wei; Zhou, Zhiyang; Chen, Li; Shuai, Cijun
Abstract: Polyetheretherketone (PEEK) is widely applied in tissue engineering due to its good biocompatibility and mechanical properties. However, the slow degradation rate limits its further application. In this study, PEEK blended with plyglycolicacid (PGA) was used to fabricate porous scaffolds via selective laser sintering. The results demonstrated that the blend scaffolds could gradually degrade, and the degradation rate was able to regulate by tailoring the PGA content. Moreover, the scaffolds maintained good biocompatibility and suitable mechanical properties. These were explained as follows: PGA on the surface layer of the scaffolds might degrade first owing to its exposure to the ambient medium. The degraded PGA left much space, which could promote cell attachment and proliferation. Meanwhile, the slow degradation of PEEK was beneficial to sustaining the scaffolds' strength and stable structure.